Lines, grids, stains, words : Minimal art drawings from the Collection of the Museum of Modern Art, New York. - Fernandes, Joao; Rattemeyer, Christian; Rattemeyer, Volker (New York : The museum of Modern Art, 2007)
Andre, Carl ; Apfelbaum, Polly ; Baer, Jo ; Barry, Robert ; Beuys, Joseph ; Bochner, Mel ; Boetti, Alighiero ; Broodthaers, Marcel ; Caldas, Waltercio ; Creed, Martin ; Darboven, Hanne ; Rivero, Elena Del ; Riverhead (New York) ; Gonzalez-Torres, Felix ; Haendel, Karl ; Hatoum, Mona ; Horn, Roni ; Horowitz, Jonathan ; Hesse, Eva ; Hume, Gary ; Judd, Donald ; Kelly, Ellsworth ; Kusama, Yayoi ; LeWitt, Sol ; Ligon, Glenn ; Lombardi, Mark ; Lozano, Lee ; Plimack Mangold, Sylvia ; Marden, Brice ; Martin, Agnes ; Mohamedi, Nasreen ; Noland, Cady ; Palermo, Blinky ; Pindell, Howardena ; Piper, Adrian ; Rockburne, Dorothea ; Roth, Dieter ; Ruscha, Edward ; Ryman, Robert ; Sandback, Fred ; Serra, Richard ; Shapiro, Joel ; Polk Smith, Leon ; Stingel, Rudolf ; Therrien, Robert ; Tiravanija, Rirkrit ; Truitt, Anne ; Wool, Christopher
Lines, grids, stains, words : Minimal art drawings from the Collection of the Museum of Modern Art, New York, MoMA (The Museum of Modern Art), New York, 2007-06-13. 2008-05-09
Lines, grids, stains, words : Zeichnungen der minimal art aus der Sammlung des Museum of Modern Art, New York, Museum Wiesbaden, Wiesbaden, 2008-06-22. 2009-01-18
Linhas, grelhas, manchas, palavras : Desenhos de arte minimalista da Colecção do Museu de Arte Moderna de Nova Iorque, Museu Serralves - Museu de Arte Contemporânea, Porto, 2008-09-28. 2007-10-22
boek